Plastic Constitutive Model and Analysis of Flow Stress of 40Cr Quenched and Tempered Steel. (5th August 2013) - Xiao-qiang, Wang; Wen-juan, Zhu; Feng-kui, Cui; Yu-xi, Li
Abstract : To solve the problem of the accuracy of the numerical simulations of cold rolling, the thermomechanical responses of 40Cr under uniaxial compression loading are presented. The strain rates include quasistatic (0.004 s −1 ) at temperature of 293 K and dynamic loading regime (632 s −1 5160 s −1 ) at temperature regime (293 K 673 K). Significant strain rate and temperature sensitivity are measured. Based on these observations, the Johnson-Cook phenomenological constitutive model is proposed to predict the mechanical behavior of the 40Cr over wide ranges of strain rate and temperature. The solution process of the equation parameters is given. Correlations with this Johnson-Cook model are shown very close to the observed responses. Important material parameters are provided to the application of numerical analysis in project.